Prescription patterns and therapeutic gaps among persons with epilepsy in Southwestern Nigeria - Luqman Ogunjimi; Bamidele Osalusi; Ayotomiwa Fagbemi; Ibironke Oyenuga; Fedora Ojini; Samuel Collins; Oluwatosin Elegbede; Olayinka Oladele; Fatai Fehintola (Frontiers Media S.A., 2024)
Introduction: Pharmacotherapy with antiseizure medications (ASMs) has been a cornerstone for achieving long-term remissions in persons with epilepsy (PWEs). This study aims to determine the prescription patterns and treatment gaps (TGs) among PWEs.Methods: Accordingly, a descriptive cross-sectional study was conducted with 940 PWEs aged ≥18 years having clinically confirmed diagnosis of epilepsy based on the International League Against Epilepsy (ILAE) criteria. At a scheduled interview with each participant, a previously established questionnaire was used to obtain clinical information relating to epilepsy in terms of the age of onset, etiology, duration of epilepsy, frequency, types, and number of ASMs used.Results: There were fewer male participants [445 (47.4%) vs. 495 (53.6%)] than females, with a higher mean age of onset [(35.19 ± 21.10 vs. 31.58 ± 20.82 years; p = 0.009]. The medication characteristics showed that 336 (35.7%) of the 940 PWEs recruited were not on any ASMs, whereas the remaining 604 (64.3%) patients were on ASMs, with 504 (83.4%) on monotherapy vs. 100 (16.6%) on polytherapy. The PWEs on ASM monotherapy had a higher mean age [40.92 ± 19.40 vs. 33.61 ± 16.51 years; p < 0.001] and higher mean age of onset [34.47 ± 21.80 vs. 25.39 ± 19.78 years; p < 0.001] than those on polytherapy. Furthermore, there were more persons on ASM monotherapy among the participants with seizure duration < 2 years [251 (87.5%) vs. 36 (12.5%)] and seizure duration > 2 years [253 (79.8%) vs 64 (20.2%)].Conclusion: The majority of the participants receiving ASMs were on monotherapy, with carbamazepine being the most frequently prescribed medication. Furthermore, about a third of the participants had TGs; therefore, healthcare providers should focus on alleviating the TGs among PWEs.